Perencanaan Penerapan Simpang Ber-APILL dengan Pendekatan PKJI 2023 Dan VISSIM (Studi Kasus: Simpang 4 Jalan Raya Mataram-Tanjung) - Mauliddah Alaras; Titik Wahyuningsih; Aulia Muttaqin (Jurnal Talenta Sipil, 2026)
The Lendang Bajur Four-Leg Intersection is one of the main intersections connecting Mataram City with the Senggigi tourism area and North Lombok, resulting in relatively high traffic volumes, particularly during peak hours. These conditions may increase traffic conflict and reduce intersection performance. This study aims to analyze the existing intersection performance and evaluate the implementation of a traffic signal system using the Indonesian Highway Capacity Manual (PKJI 2023) and PTV VISSIM simulation software. The research began with traffic volume surveys and geometric measurements, followed by analyses of capacity, degree of saturation, delay, and signal cycle time based on PKJI 2023. The proposed signal timing was subsequently modeled using PTV VISSIM to evaluate the operational performance of the intersections. The analysis produced an optimum signal cycle time of 49 seconds, with an average approach delay ranging from 21.26 to 34.21 seconds per vehicle. The VISSIM simulation indicated that several traffic movements still experienced relatively high vehicle delays due to traffic movement characteristics and operational conditions at the intersections. The differences between PKJI 2023 and PTV VISSIM results are attributed to their different analytical approaches, indicating that both methods complement each other in evaluating intersection performance. The findings are expected to provide a reference for planning signalized intersections with similar traffic characteristics.